Biofármacos no Brasil: Características, importância e delineamento de políticas públicas para seu desenvolvimento - Mario Sergio Salerno; Cristiane Matsumoto; Isabela Ferraz (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The text discusses possibilities of public policies for the development of biopharmaceuticals in Brazil, with emphasis on monoclonal antibodies (mAbs). First section discusses the basic concepts about biotechnology, biopharmaceuticals and monoclonal antibodies in order to sustain the later development of the work. Next, it discusses the evolution of the global pharmaceutical industry, emphasizing biopharmaceuticals, its value chain and general industry challenges. Then, it discusses the Brazilian scenario, emphasizing industry structure, demand, mainly of SUS (Brazilian Health System), regulation and actors involved in the chain or value network. Finalizing the text, a discussion on possibilities and alternatives for the development of public policies that help to leverage the development of this relevant industry.
Keywords: O38; L65; 330; biopharmaceuticals; drug innovation; public policy